2013
DOI: 10.1111/bph.12054
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide protects against cigarette smoke‐induced oxidative lung injury via augmentation of Nrf2 activity

Abstract: BACKGROUND AND PURPOSECigarette smoke is a major cause for chronic obstructive pulmonary disease (COPD). Andrographolide is an active biomolecule isolated from the plant Andrographis paniculata. Andrographolide has been shown to activate nuclear factor erythroid-2-related factor 2 (Nrf2), a redox-sensitive antioxidant transcription factor. As Nrf2 activity is reduced in COPD, we hypothesize that andrographolide may have therapeutic value for COPD. EXPERIMENTAL APPROACHAndrographolide was given i.p. to BALB/c m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 57 publications
5
56
0
1
Order By: Relevance
“…Activation of Nrf-2 by triterpenoids, such as CDDO-imidazolide, has demonstrated beneficial effects in a cigarette smoke induced emphysema animal model [30]. Our results showed that CS exposure enhanced the expression and activity of Nrf-2, which is consistent with the previous studies [31]. CS-induced upregulation of Nrf-2 mRNA, and nuclear Nrf-2 protein was significantly enhanced by emodin pretreatment.…”
Section: Discussionsupporting
confidence: 91%
“…Activation of Nrf-2 by triterpenoids, such as CDDO-imidazolide, has demonstrated beneficial effects in a cigarette smoke induced emphysema animal model [30]. Our results showed that CS exposure enhanced the expression and activity of Nrf-2, which is consistent with the previous studies [31]. CS-induced upregulation of Nrf-2 mRNA, and nuclear Nrf-2 protein was significantly enhanced by emodin pretreatment.…”
Section: Discussionsupporting
confidence: 91%
“…Andrographolide has been shown to up‐regulate Nrf2‐dependent HO‐1 expression and prevent oxidative damage (Guan et al ., ), and to inhibit TNF‐α‐induced expression of intercellular adhesion molecule (Yu et al ., ). To determine whether andrographolide affects the expression of HO‐1 gene in HCV replicon cells, we initially tested the effect of andrographolide on HO‐1 gene transcription using a transient HO‐1 promoter‐based reporter assay.…”
Section: Resultsmentioning
confidence: 99%
“…A. paniculata has long been used as herbal medicine for the prevention and treatment of upper respiratory tract infection in Asian countries and in Scandinavia (14). Andrographolide has been shown to possess various biological activities, including antiviral (15), anticancer (13,16), anti-inflammatory (17,18) and antioxidative (15,19,20) activities.…”
mentioning
confidence: 99%